Assessment of the Efficiency of the Financial Mechanism of Environmental Management - Labenko, Oleksandr; Lymar, Valeriia; Faichuk, Olha; Dolzhenko, Inna; Hutsol, Taras; Белей (Belei), Cвітлана (Svitlana); Parafiniuk, Stanisław; Kwasniewski, Dariusz; Tabor, Sylwester; Kiurcheva, Lyidmila (Sciendo is a De Gruyter Brill company, 2024)
In recent decades, cataclysmic events, deterioration of air and water quality, and loss of biodiversity have forced us to look for ways to save nature. One of the ways to solve the problems is to ensure rational environmental management, which is possible by establishing an effective balance between consumption and compensation by creating an effective financial mechanism. The purpose of the study is to assess the efficiency of the current financial mechanism for environmental management in Ukraine and to determine the prospects for its improvement. The study uses analysis, synthesis, specification, systematization, and generalization. The graphical method was used to assess environmental taxes, and mathematical modelling was used to analyze the dependence of emissions on direct costs and capital investments in air protection and climate change. Environmental taxes in Ukraine are an ineffective instrument of the financial mechanism of environmental management. Their share in the structure of domestic GDP is lower than the share in the EU. The author suggests ways to improve them: to replace the CO2 tax with an energy tax; to cancel the tax-free limit of 500.000 tons of CO2 emissions per year; to change the structure of tax distribution; to introduce tax rebates. The correlation and regression analysis of the dependence of air pollutant emissions on current expenditures and capital investments in air protection and climate change issues showed the existence of a feedback loop. Investment support for environmental management should be provided from various sources in the following areas: national, local and international finances - primarily for the restoration of air, water and contaminated areas; own funds and international investments - for the modernization and greening of production
Assessment of the Efficiency of the Financial Mechanism of Environmental Management
Keywords: financial mechanism of environmental management, financial regulation, environmental taxes, environmental taxes, production